Protective Effects of Mackerel Protein Hydrolysates Against Oxidative Stress-Induced Atrophy in C2C12 Myotubes - Gyu-Hyeon Park; Syng-Ook Lee (Foods)
Muscle aging and atrophy in the elderly are closely associated with increased oxidative stress in muscle tissue. Bioactive peptides derived from protein hydrolysates have emerged as promising functional ingredients for alleviating sarcopenia due to their antioxidant properties and enrichment in essential amino acids. In a preliminary screening, mackerel protein hydrolysate (MPH) showed notable protective effects in a myotube atrophy model. This study evaluated the anti-atrophic potential of MPHs produced using different enzymes in H2O2-treated C2C12 myotubes. Among five hydrolysates, the alcalase-derived hydrolysate (MHA) demonstrated the most potent effects in maintaining myotube diameter, restoring myosin heavy chain (MYH) expression, and downregulating the atrophy-related genes MAFbx and MuRF1. Mechanistically, MHA activated the Akt/FoxO signaling pathway and inhibited NF-κB activation, thereby reducing muscle protein degradation. Additionally, MHA significantly lowered intracellular ROS levels and showed strong direct antioxidant activity. Amino acid and molecular weight profiling revealed high levels of essential amino acids and low-molecular-weight peptides, suggesting a synergistic contribution to its bioactivity. These findings suggest that MHA is a promising food-derived functional material with anti-atrophic and antioxidant properties and may be useful in preventing or managing age-related muscle loss such as sarcopenia, warranting further preclinical validation.